2020
DOI: 10.1080/00207543.2020.1823028
|View full text |Cite
|
Sign up to set email alerts
|

Workforce reconfiguration strategies in manufacturing systems: a state of the art

Abstract: This paper provides a literature review and an analysis of the studies related to workforce reconfiguration strategies as a part of workforce planning for various production environments.The survey demonstrates that these strategies play a crucial role in the resilience and flexibility of manufacturing systems since they help industrial companies to quickly adapt to frequent changes in demand both in terms of volume and product mix. Five strategies are considered: the use of utility, temporary, walking, cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 172 publications
0
10
0
Order By: Relevance
“…-in (Gualtieri et al, 2020c) only safety (as cobot capability) and ergonomics (as human factors) have been considered. The other HFs and the characteristics of Industry 4.0 were not included in the research; -in (Hentout et al, 2019) safety and security and natural language were investigated but a classification of social factors wasn't proposed; -in (Matheson et al, 2019) an overview of human robot classification was carried out but this work fails in the analysis of the relation between human operations and cobots in terms of the features of Industry 4.0 technologies; -in (Wang et al, 2019) human teaching and robot learning techniques were investigated, without considering the modern production systems repercussions; -in (Zarte et al, 2020) the authors identified the notions for a human-centered architecture but cobot capabilities and Industry 4.0 characteristics were not included; -in a review on wereable sensor and contactless gesture control was carried out to improve the ergonomics in human robot collaboration: this means that all the other HF were not taken into account: -in (Schneier et al, 2015) -in (Hashemi-Petroodi et al, 2020) wasn't considered how the interaction of human operators and cobots affects the features of Industry 4.0;…”
Section: Comparison With Other Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…-in (Gualtieri et al, 2020c) only safety (as cobot capability) and ergonomics (as human factors) have been considered. The other HFs and the characteristics of Industry 4.0 were not included in the research; -in (Hentout et al, 2019) safety and security and natural language were investigated but a classification of social factors wasn't proposed; -in (Matheson et al, 2019) an overview of human robot classification was carried out but this work fails in the analysis of the relation between human operations and cobots in terms of the features of Industry 4.0 technologies; -in (Wang et al, 2019) human teaching and robot learning techniques were investigated, without considering the modern production systems repercussions; -in (Zarte et al, 2020) the authors identified the notions for a human-centered architecture but cobot capabilities and Industry 4.0 characteristics were not included; -in a review on wereable sensor and contactless gesture control was carried out to improve the ergonomics in human robot collaboration: this means that all the other HF were not taken into account: -in (Schneier et al, 2015) -in (Hashemi-Petroodi et al, 2020) wasn't considered how the interaction of human operators and cobots affects the features of Industry 4.0;…”
Section: Comparison With Other Literature Reviewmentioning
confidence: 99%
“…Indeed, due to the growing interest in collaborative applications, in the last years some literature reviews have been proposed, such as (Matheson et al, 2019;Wang et al, 2019;Gualtieri et al, 2020c;Hentout et al, 2019;Hashemi-Petroodi et al, 2020) . However, these works fails at studying the complex interaction of human operators and cobots in terms of modern production systems, i.e., how this interaction affects the features and the requirements of I4.0 technologies.…”
Section: Introductionmentioning
confidence: 99%
“…This family is composed of products K7-K1-K8, and this is the first iteration of creating a product family in the proposed methodology. The required number of machines 𝑞𝑞 𝛼𝛼 𝑝𝑝 = 44, was calculated for the mentioned family, while this value will be increased by one (25) in the form of warm or cold backup. The product configuration equipment also mentioned will consist of eight operating stages "i".…”
Section: Resultsmentioning
confidence: 99%
“…Article [24] deals with the analysis and control of dynamic reconfiguration process of manufacturing systems from the perspective of discrete event systems. Article [25] provides a literature review and an analysis of the studies related to workforce reconfiguration strategies as a part of workforce planning for various production environments.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded in their discussion they concluded that their results might have been different if they would have introduced additional dependent variables such as service quality. Another study by Hashemi-Petroodi et al (2020) highlighted that temporary workers can be used as complementary to permanent workers; however, they refer to workforce assignment problems due to the differences in skill levels. In seasonal or uncertain demand, the use of temporary workers may improve the responsiveness of a manufacturing system, but there are possible trade-offs in the form of product quality.…”
Section: Temporary Work and Quality Performancementioning
confidence: 99%